Endovascular Treatment of Abdominal Aortic Aneurysm with Complete Iliac Occlusion: Case Series and Literature Review - Franz, Randall W.; Ibrahim, M. Taha; Tanga, Christopher F.; Epstein, David A. (International Journal of Angiology, 2017)
In patients with abdominal aortic aneurysms (AAA) and complete iliac occlusion, endovascular aortic aneurysm repair (EVAR) using a bifurcated stent graft has clear advantages over aortouniiliac stent grafts. Bifurcated stent grafts had improved hemodynamic flow and increased primary and secondary patency rates compared with aortouniiliac stent grafts. The use of aortouniiliac stent grafts with femorofemoral crossover bypass is associated with complications including infection of the prosthesis, steal phenomenon, and the associated difficulties for further endovascular access at the site of the femoral anastomosis. Recanalization of occluded iliac arteries at the time of EVAR avoids the complications mentioned above. We report three cases of patients with AAA and iliac occlusion who were successfully treated with iliac recanalization at the time of EVAR.
Keywords: abdominal aortic aneurysm; aneurysm; angioplasty; endovascular repair; iliac artery disease; iliofemoral occlusive disease; peripheral arterial disease